PENGARUH STRATEGI PEMASARAN VIRAL YANG MEMPENGARUHI NIAT BELI BAGI KONSUMEN SKINTIFIC - Theresia Viony Wijaya; Hetty Karunia Tunjungsari (Jurnal Serina Ekonomi dan Bisnis, 2023)
This research is conducted the ef ect of viral marketing strategies on Skintific's purchase intention for consumers:the value of fish as mediation. This research used non-probability sampling through convenience sampling to obtain228 respondents who are Skintific skincare users. Data collection was carried out online by distributingquestionnaires via Google Forms. Data was processed using the Partial Least Square Structural Equation Modeling(PLS-SEM) method with SmartPLS 4.0 software. The results showed that viral marketing strategies in the form ofEntertainment, Informativeness and Source Credibility had a positive and significant ef ect on Advertisement Value,while there was a negative and insignificant ef ect of viral marketing strategies on Advertisement Value. Besidesthat, there is a positive and significant influence from Entertainment and Informativeness on Purchase Intention.And Advertisement Value mediates the two relationships between Entertainment and Purchase Intention Skintificpositively and significantly, Advertisement Value also mediates the two relationships between Source Credibility andPurchase Intention Skintific positively and significantly, Advertisement Value also mediates both relationshipsbetween Irritation and Purchase Intention Skintific negatively and not significant, and Advertisement Value alsomediates the relationship between Source Credibility and Purchase Intention Skintific in a positive and significantway.